Prognostic value of the systemic immune-inflammation index in bladder cancer: an update evidence-based analysis - Bai, Jingxing; Huang, Yin; Chen, Bo; Ran, Biao; Jian, Shibo; Li, Jinze; Chen, Jie; Wei, Qian; Cao, Dehong; Liu, Liangren (Frontiers in Oncology, 2025)
BackgroundBladder cancer (BC) prognosis remains challenging to predict accurately with conventional tools. Systemic immune-inflammation index (SII) has emerged as a promising biomarker reflecting the tumor microenvironment. However, existing studies are limited by small sample sizes, heterogeneous designs, and inconsistent endpoints. This updated meta-analysis aims to comprehensively evaluate the association between high SII and key survival outcomes in BC patients.MethodsWe systematically searched PubMed, Embase, Web of Science, and Cochrane up to August 2025. Cohort studies reporting hazard ratios (HRs) for overall survival (OS), recurrence-free survival (RFS), progression-free survival (PFS), or cancer-specific survival (CSS) comparing high vs. low SII groups in histologically confirmed BC were included. Study quality was assessed using the Newcastle-Ottawa Scale. Pooled HRs with 95% confidence intervals (CIs) were calculated using a random-effects model. Subgroup analyses by pathological type (NMIBC vs. MIBC) and sensitivity analyses were performed. Publication bias was evaluated via funnel plots and Egger’s test.ResultsSixteen cohort studies involving 2,352 patients were analyzed. Meta-analysis revealed that elevated SII was significantly associated with worse OS (HR=1.66, 95% CI: 1.30–2.12, P < 0.0001) and RFS (HR=1.50, 95% CI: 1.28–1.76, P < 0.00001), with substantial heterogeneity (OS: I² = 81%; RFS: I² = 59%). Subgroup analysis showed significant predictive value of SII for RFS in both NMIBC (HR=1.55, 95% CI: 1.27–1.89, P < 0.0001; heterogeneity reduced to I² = 37%) and MIBC (HR=1.13, 95% CI: 1.01–1.26, P=0.03). However, OS subgroup associations for NMIBC (HR=1.15, P=0.50) and MIBC (HR=1.92, P=0.07) were non-significant. No significant associations were found for PFS (HR=1.55, 95% CI: 0.92–2.60, P=0.10, I² = 68%) or CSS (HR=1.50, 95% CI: 0.95–2.37, P=0.08, I² = 69%), likely due to limited study numbers (4 and 3, respectively). Significant publication bias was detected for OS and RFS.ConclusionElevated SII is significantly associated with poorer overall and recurrence-free survival in bladder cancer patients, particularly highlighting its potential predictive value for recurrence risk in NMIBC. However, significant heterogeneity, publication bias, and retrospective design limitations necessitate caution in interpretation. Future large-scale, prospective studies with standardized SII measurement and dynamic monitoring are crucial to validate its clinical utility and define optimal cut-offs for integration into risk-stratified management strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251145769, Prospero identifier, CRD420251145769.